Friday

December 19, 2014

December 19, 2014

Posted by **Jus** on Tuesday, May 19, 2009 at 8:27pm.

log_b (a) = c, and log_y (b) = c, then log_a (y)=c^-2

- Math -
**Reiny**, Tuesday, May 19, 2009 at 8:34pm

**Answer this Question**

**Related Questions**

Exponential Functions - Show that if log_b (a) = c, and log_y (b) = c, then ...

math - Solve this equation. Verify your solution using a graphing utility. log_a...

ALGEBRA - Select all statements that are true. (log_b\(A\))/(log_b\(B\))=log_b\(...

algebra - 2. The level of thorium in a sample decreases by a factor of one-half ...

ALGEBRA - (log\(A\))/(log\(B\)) = (ln\(A\))/(ln\(B\)) (log_b\(A\))/(log_b\(B\))=...

Algebra Help - Express in terms of sums and differences of logarithms: log_a x^3...

Math - Logarithmic - Is the following correct when restating logs with variables...

math - if a & b are perpendicular vectors, show that a)(a+2b).(a-b)=|a|^2-2|b|^2...

math - Can someone please show us how to show 1500 x 2.1? I can not for the life...

math - a local television station sends out questionnaires to determine if ...